Pengaruh stresor psikososial terhadap depresi dan gangguan kesehatan reproduksi guru perempuan Sekolah Dasar negeri - Sumarni DW, Maulina DS (Fakultas Kedokteran Universitas Gadjah Mada, 2006)
Background: In order to perform their duties, slate-owned elementary school female teachers face heavy burden. Demands for high professionalism, to be a good housewife role, and to be a good society member can be psychosociai stressors that affect their depression and reproduction health disorder, and decline their performance and productivity.Objectives: To find out the effect of psychosocial stressor on depression and reproduction health disorder on state-owned elementary school female teachers in Kota Yogyakarta.Material and Methods: This study was observational, designed as a cross sectional study, conducted on 84 stale-owned elementary school female teachers in Kota Yogyakarta. Instruments used were SRRS, CES-D 20, urinalysis equipments, and equipments for pap-smear examination. Data were statistically analyzed using regression method and Pearson's product moment correlation.Results: The dominant psychosocial stressor faced by the slate-owned elementary school female teacher was psychosocial stressor from their work surrounding. The prevalence of depression was 54,7%; menstruation disorder 77,4%; urethra disorder 69,0%; coitus disorder 60,7%; pektay 70,2%; and pregnancy disorder 8,3%. There was a significant effect of psychosocial stressor on depression (R2 = 0, 8248) and reproduction health disorder (R2 = 0,4995).Conclusions: The dominant psychosocial stressor faced by the state-owned elementary school female teacher was psychosocial stressor from their work surrounding. There was a significant effect of psychosocial stressor on depression and reproduction health disorder. Keywords: psychosocial stressor, depression, reproduction health disorder, state-owned elementary school female leacher